Partisipasi Masyarakat dalam Kegiatan Rehabilitasi Hutan dan Lahan di Hutan Lindung - Yunita Delna; Reflis Reflis; Yurike Yurike; Indra Cahyadinata; Satria Putra Utama (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2026)
The flash floods accompanied by landslides in 2019 in the Lemau watershed area caused the loss of effective forest vegetation area, which can reduce soil moisture, evapotranspiration, infiltration, and increase surface runoff. This study aims to identify the level of community participation in Forest and Land Rehabilitation (RHL) activities in the Bukit Daun Protected Forest Area, Central Bengkulu Regency and examine the relationship between factors that influence the level of community participation in these activities. The data analysis method for the first objective was carried out through data formulation and classification to obtain meaningful interpretations, while the second objective was analyzed using Structural Equation Modeling (SEM) with Partial Least Square (PLS). Respondents were selected using a purposive sampling technique of 55 people. The results showed that the level of farmer participation in forest and land rehabilitation activities in Susup Village reached an average score of 4.29. The results of the SEM analysis show that the variables of dialogue, conveying aspirations (voice), dialogue to channel aspirations (liberating pedagogy), and reflecting on problems and actions (action-reflection-action) have a positive and significant effect on community participation in forest and land rehabilitation activities. For forest and land rehabilitation activities, it is necessary to increase environmental education and awareness through ongoing environmental socialization and education, which is important to raise public awareness about the long-term benefits of forest and land rehabilitation, so that participation is not only temporary, but becomes a shared culture. There needs to be strengthening of regulations and support from regional and central government policies to ensure the existence of rules that support post-rehabilitation forest protection and provide incentives for participating communities.